Pragmatic persuasion in English and Uzbek ads: Speech acts, implicature, cultural adaptation - Sherkulova Makhliyo Khasan Kizi (Goodwood Publishing, 2026)
Purpose: The purpose of this study is to analyze pragmatic persuasive strategies in English and Uzbek advertisements, with a focus on how speech acts, conversational implicature, and cultural adaptation function in shaping promotional discourse. Research Methodology: The study employed a qualitative comparative analysis of 200 advertisements (100 English, 100 Uzbek). Data were categorized according to Searle’s speech act taxonomy and Grice’s implicature framework, complemented with an examination of cultural adaptation strategies. Results: Findings indicate that English advertisements favor direct speech acts and universal implicature, emphasizing clarity and individual empowerment. By contrast, Uzbek advertisements rely more on indirect speech acts, culturally embedded implicature, and adaptation mechanisms aligned with collective values and respect for hierarchy. Conclusions: Successful cross-cultural advertising requires sensitivity to pragmatic norms and cultural expectations, as literal translation alone does not achieve persuasive effectiveness. Limitations: The research is limited to selected English and Uzbek advertisements and may not generalize to all advertising contexts. Contribution: This study contributes to pragmatics, translation studies, and advertising discourse analysis by offering theoretical insights and practical recommendations for cross-cultural adaptation in global communication.